Dulux Wall Paint Purchase Decision: The Role of Brand Image, Price, And Product Quality on Consumer Behavior of Paint Products (Jurnal Simki Economic, 2021)
Increased economic growth affects consumer needs. Consumer needs for buildings, not only based on its function but also its beauty. One of them is the need for paint. This study aims to determine the effect of brand image, price, and product quality on purchasing decisions. The population of this study is the consumers of Dulux wall paint in the city of Surabaya. The sample of this study consisted of 100 respondents. The sampling technique used the Accidental Sampling method. The analysis technique used is multiple linear regression. The results showed that brand image, price, and product quality partially had a significant influence on purchasing decisions. In addition, brand image, price, and purchasing decisions have a significant role in simultaneous purchasing decisions.